Incidence and Study of Sociodemographic Factors & Other Risk Factor fors Pelvic Organ Prolapse - Haque, Fahmida; Sarker, Sharmila (Sir Salimullah Medical College Journal, 2022)
Backgound: The burden of pelvic organ prolapse in parous women is enormous. Bangladeshi women suffers a lot due to (POP) pelvic organ prolapse. Minor prolapse or laxity is generally ignored. When serious functional disability develops, women seek treatment advice. Home delivary and subinvolutions during puerperium is thought to predispose to urogenital prolapse. Here the incidence of different degree of prolapse and associated risk factors are assessed. Materials and method; This prospective observational study was carried out in outpatient department of gynaecology and obstetrics of SSMCMH during the period of January 2018 to September 2018. 100 parous women with subjective symptom of prolapse were included. Degree of prolapse and related risk factors were identified. Results: Here 53% had Pelvic Organ Prolapse Quantification System (POP-Q) grade 1,32% had grade II and 15% had grade III and IV. Majority showed anterior vaginal wall defect. Cystocoele was 77% and perineal tear was 79%. Rectocoele was also present in 60% cases. Risk increases with increasing age 45% was >60 years. Multipara (>4 child) had the highest incidence. Also H/O home delivery, delivery by untrained personal, puerperial unusual work load increases the risk. Conclusion : POP is a common condition. Here the prevalence of grade I and II were high. But grade III and IV requiring surgical treatment among the women was 12% and 3% respectively .Incidence rises with increasing age, parity, prolonged and difficult labour . Birth spacing <2 years and neglected puerperial period also contribute. Sir Salimullah Med Coll J 2022; 30: 129-132